Information Technology in Bio- and Medical Informatics 5th International Conference, ITBAM 2014, Munich, Germany, September 2, 2014. Proceedings - Bursa, Miroslav; Khuri, Sami; Renda, M. Elena (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the refereed proceedings of the 5th International Conference on Information Technology in Bio- and Medical Informatics, ITBAM 2014, held in Munich, Germany, in September 2014, in conjunction with DEXA 2014. The 9 revised long papers presented together with 3 short papers were carefully reviewed and selected from numerous submissions. The papers address the following topics: clustering and bioinformatics; medical image and data processing; and knowledge discovery and machine learning in medicine.